Pengaruh Sistem Rekrutmen dan Pengembangan Karir terhadap Prestasi Kerja Pegawai - Ardhaswari Putri, Desak Putu Krissila; Kawiana, I Gede Putu; Sunny, Milla Permata (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study is to assess the impact of the recruitment and career development system on job performance. This research employs a quantitative approach and was carried out at PT BPR Tish Batubulan with a total population of 38 employees. A saturated sampling technique was used, meaning all members of the population were included as research subjects. Primary data were gathered through a questionnaire, and hypothesis testing was performed using multiple linear regression analysis. The findings indicate that: 1) the recruitment system positively and significantly influences job performance, 2) career development positively and significantly affects job performance, and 3) the combined recruitment and career development system has a positive and significant impact on job performance. In improving work performance, PT BPR Tish Batubulan is expected to be able to announce job vacancies by developing wider social media so that it is possible to get more quality applicants and then improve the employee career development sector by holding promotion programs for every employee who has excellent work performance. both by paying attention to and making aspects of employee honesty one of the main considerations.